Longer School Schedules and Early Reading Skills: Effects from a Full-Day School Reform in Chile - Matias Berthelon; Diana Kruger; Veronica Vienne (Institute for the Study of Labor (IZA), 2016)
This paper analyzes the impact of longer school schedules on children's 2nd grade reading comprehension skills in Chile. In a setting where families choose schools, we identify the causal effect of longer schedules with instrumental variables, using the local availability of full-day schools as an instrument. We find that lower-income families are more likely to choose full-day schools, and after controlling for selection, longer school schedules lead to an increase of 0.14 standard deviations in reading comprehension. Effects are heterogeneous, with greater benefits among children attending public (municipal) and urban schools, and among girls. We also find that the benefits of longer school days accumulate over time.
Keywords: I21; I28; I26; H43; 330; reading comprehension skills; full-day schooling; school schedules; SIMCE; Chile